Prevalence of the Theory of Unity of Title of Imputation: Determination of the Legal Nature of the Extraneus in the Crime of Collusion - Lorenzo Pérez Livia (2021)
This topic has didactic importance for the study of Criminal Law specifically in the crime of Collusion, contributing to the formation of correct interpretation of the norm of indicated discipline, it serves as support in the performance of the practical work of Law operators. However, this relevance is not very significant due to the few scientific works that have addressed this issue. Within these limits, this document seeks to establish Legal Foundations that support the Prevalence of the Theory of the Unit of the Imputation Title in the determination of the legal nature of the extraneus in the crime of Collusion. From a descriptive model, conversation analysis and doctrinal review, the main results show that the prosecution of the extraneus under the Theory of the Unit of the Imputation Title in the crime of Collusion, guarantees the fulfillment of the public purpose of the criminal process in a manner full, inasmuch as it determines the same criminal responsibility to the intraneus and the extraneus; it also allows to repress the behavior under the approach of the theory of general prevention, as well as guarantees the reparation of the affected treasury to the State.